One Size Does Not Fit All: Distinct Solutions for Distinct Needs - Advisory Board on English Education (2013)
In this report to the Minister, the Advisory Board on English Education is taking the opportunity to review the themes and concerns identified in earlier correspondence, reports and briefs that continue to describe English education in Québec accurately, and to update them with current examples of both concerns and successes. We emphasize that there is no intention to promote one system over another, nor to assign fault. We believe that many of the inherent difficulties faced by English school boards, schools and centres could be mitigated if MELS were to take better account of the differences between the two sectors in its policies and their implementation. It is hoped that a description of the distinctiveness of the English sector and how it functions differently from the French sector will provide some insight as to how the English system is frequently constrained by many of the Ministry’s policies, especially in their application, and indicate the need for flexibility in implementing policy. This will ensure that the English education system can continue to prepare its graduates to participate fully in the life of Québec society.

Canada, Bilingualism and Trade - Arcand, Alan; The Conference Board of Canada (Community Economic Development and Employment Corporation (CEDEC), 2013)
The French language is one of the world’s major languages. According to L’Organisation internationale de la Francophonie (OIF), at least 220 million people in the world speak French. It’s the official language of all United Nations agencies and a large number of international organizations. The language originated in France and spread by way of the country’s overseas expansion. Today, some 30 countries in the world, including Canada, have recognized French as an official language.